Growth and Yield Evaluation of Avocado (Persea americana) Varieties in Lowland Agro Ecology of Raya Azebo, Southern Zone of Tigray Region, Northern Ethiopia - Haile Abebe; Wakuma Biratu; Kidane Tesfay; Molla Berhe; Haileselassie Gebremeskel (Agro Bali : Agricultural Journal, 2022)
Avocado is among the subtropical fruit crops produced in Ethiopia; however, the production and Productivity of avocado is influenced by different factors; of which lack of improved and well adapted varieties are the major one. So, an experiment was conducted at Fachagama from 2013 to 2019 to evaluate and select the best adaptable avocado variety/ies at Raya Valley. Six avocado varieties namely Ettinger, Fuerte, Pinkarton, Hass, Naba and Bacon were laid in RCBD and replicated three times. To achieve the objective, the growth, phenological and yield data were collected and analyzed using SAS software.  Accordingly, above graft union stem girth diameter was significantly (P≤0.01) affected by variety, while tree height and canopy diameter were not significantly ascertained by variety. All the tested avocado fruit yield parameters were significantly (P≤0.01) influenced by variety throughout the three years except marketable fruit yield tree-1 and the total yield tree-1 which was not significantly (P≥0.5) determined by variety during 2017 fruit harvesting year. Variety exerted significant (P≤0.01) variation on fruit length (cm) fruit weight (g) and seed weight respectively, throughout the three years (2016-2018), the two years (2017 and 2018) and the two years (2016 and2018). The highest girth diameter (61.44mm) was obtained on Nabal variety. Likewise, the highest (15.51 and18.88kg tree-1) total yield was recorded in Pikerton and Bacon varieties respectively during 2016 and 2018 respectively. From the result Pinkerton and Bacon are recommended for Raya Valley and other areas having similar agro-ecologies.  However, it is important to consider the water requirements in terms of irrigation depth and frequency of avocado.